Strengthening Collaboration Between Financial Institutions and Universities to Empower a Sustainable Economy - Waeno, Mahamadaree; Mushlihin, Imam Annas; Natalina, Sri Anugrah; Sulistyowati, Sulistyowati; Samsuri, Ali; Fauza, Nilna; Zainuddin, Moch; Zunaidi, Arif; Mutafarida, Binti; Utama, Yopi Yudha (Welfare : Jurnal Pengabdian Masyarakat, 2024)
Efforts to strengthen collaboration between financial institutions and universities are a key step in empowering a sustainable economy. This service activity aims to increase cooperation between financial institutions and universities, with a focus on sustainable economic empowerment. The service method is carried out through holding international seminars in a hybrid manner, both face-to-face at the Library Building on the 4th floor of IAIN Kediri and via the Zoom platform. The results of this service include strengthening cooperation between the two entities, broadening students' insight into sustainable financial practices, and contributing to sustainable economic development on campus and in the surrounding community.